2002
DOI: 10.1017/s1355838202013262
|View full text |Cite
|
Sign up to set email alerts
|

Highly conserved NIKS tetrapeptide is functionally essential in eukaryotic translation termination factor eRF1

Abstract: Class-1 polypeptide chain release factors (RFs) play a key role in translation termination. Eukaryotic (eRF1) and archaeal class-1 RFs possess a highly conserved Asn-Ile-Lys-Ser (NIKS) tetrapeptide located at the N-terminal domain of human eRF1. In the three-dimensional structure, NIKS forms a loop between helices. The universal occurrence and exposed nature of this motif provoke the appearance of hypotheses postulating an essential role of this tetrapeptide in stop codon recognition and ribosome binding. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 28 publications
5
135
0
Order By: Relevance
“…Structural studies of human RF1 suggest that its N-terminal domain interacts with mRNA during stop codon recognition (30). Numerous studies demonstrated that the sequences near the highly conserved NIKS motif in this domain are critical for stop codon recognition (31)(32)(33). If UAG codons were reassigned to code for Pyl in Pyl-containing archaea, their release factors would have specific changes responsible for the alteration of their specificity.…”
Section: Analysis Of Class I Release Factors In Archaeamentioning
confidence: 99%
“…Structural studies of human RF1 suggest that its N-terminal domain interacts with mRNA during stop codon recognition (30). Numerous studies demonstrated that the sequences near the highly conserved NIKS motif in this domain are critical for stop codon recognition (31)(32)(33). If UAG codons were reassigned to code for Pyl in Pyl-containing archaea, their release factors would have specific changes responsible for the alteration of their specificity.…”
Section: Analysis Of Class I Release Factors In Archaeamentioning
confidence: 99%
“…It was proposed that the N and M domains could form a functionally active "core" domain (Frolova et al, 2000). Possibly, all domains contain ribosome-interacting sites (Eurwilaichitr et al, 1999;Frolova et al, 1999Frolova et al, , 2002.…”
Section: Eukaryotic Release Factors 1 (Erf1)mentioning
confidence: 99%
“…The ciliate-specific diversity at TAS and NIKS sites also has been pointed out independently (1,22,23). Recently, the role of NIKS motif in RF activity and ribosome binding has been shown for human eRF1 in in vitro experiments (24). Therefore, it is tempting to speculate that the TASNIKS heptapeptide region is functionally essential and can modulate stop codon discrimination in eukaryotes.…”
mentioning
confidence: 91%